A Neurological Disease, Vathatvartma (Ptosis), Managed with Integrated Management of Modern Science and Ayurveda – A Case Report - Roshna Bhutada; Mitali S. Rathi (Journal of Pharmacy and Bioallied Sciences)
Introduction: Ptosis is when the upper eyelid droops downward. However, a droopy eyelid can cover the pupil and reduce vision in some cases. Causative factors may be congenital, injury or stretching of eyelid muscles or ligaments damage to the nerve controlling the eyelid muscles, aging, a complication of eye surgery, a complication of Botox injections. Aim and objectives: To study case of ptosis with integrated treatment of neurologist along with Ayurveda treatment. Methodology: Case Description - This is a 34year old female patient complaining that she is unable to open her right eye since11 days. She visited to local ophthalmologist, then they have consulted neurologist, MRI done, treatment started, at the same time patient wants to take Ayurveda treatment also. After 7th day visit to neurologist, she has stopped his medicine and told to continue alternative treatment So she consulted at MGACH&RC Salod on 4/3/2022. Her V/A right eye after uplifting upper lid by doctors hand is 6/6 and lt eye v/A is 6/6. Fundus of both was within normal limit. No diplopia, Acute onset with fronto orbital pain, pupil NSRL, conjugate left downgaze movement restricted. Result and Discussion: treatment prescribedshirodhara with brahmi and til tail, netratarpan with triphalaghruta, Tab Palsineuron 2 bd, Tab Ekangvirras 2 bd. - vatashamak Chikitasa is done as ptosis is neurological disease.after 7th day visit to neurologist, he has stopped his medicine and told to continue alternative treatment. Conclusion: The results were enthusiastic photographic depiction were taken. This case may be fruitful for further research on Nimesh/ Ptosis.